Sistem Penyimpanan Metadata Objek 3 Dimensi - Eka Yudistira Sugiono (Melek IT : Information Technology Journal, 2016)
A three-dimensional object that metadata secretly.To show you the 3d metadata of the object must use of software.However, the increasingly complex three-dimensional objects are in need of a lot of time and needs access speed which is quite big for the vault.This will simplify metadata to 3 dimensions of objects with the aim of that metadata to simplify the 3d penyimpanana access to speed up the process and do not need 3d membutuh along time.Following the reserve system is metadata three-dimensional object on it the resulting trial is metadata can be selected based on standard after standard metadata metadata was chosen to be on the market in line with the original.